(168) the applicability and utilization of input - output model in a developing economy - eliesh, G. (the institute of national planning, 2018)
so far tow input- out table have been constructed for the Egyptian economy, one for the year 1954 and the other for the year 1959. in this paper reference will only be made to the 1954 table, and aggregated version of which is included in the appendix.